Teamwork Approach in Lifestyle Modification in a Health Clinic: A Perspective Study - Masoud Ferdosi; Majid Kolahdouzan; Behnaz Nikkar Isfahani; Arman Kolahdouzan; Mohammad Shayan Kolahdouzan (Shahid Sadoughi University of Medical Sciences, 2021)
Chronic diseases have become an acute challenge in health. Providing a framework for the transformation of services could be very helpful. In this study, the teamwork services based on lifestyle modification used in a series of Health Clinics in Isfahan (Iran); have been reported as a desirable method in the treatment of metabolic Syndromes. "Iranian Health Clinics" have been providing services in the fields of lifestyle modification, promoting healthy lifestyles, diagnosing and treating metabolic syndromes such as diabetes, hypertension, hyperlipidemia, as well as weight regulation and stabilization. This clinic series offers its services as a team of psychologists, nutritionists, physical trainers, and physicians. Treatment of metabolic syndromes by the team-based method as well as continuing contact with patients in the courses of treatment, stabilization, and training of health ambassadors can be instrumental in consolidating the results using this framework in the control of metabolic syndromes.